A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters. Issue 1 (October 2016) - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf
Abstract: This work employs a fuzzy finite element method (FFEM) in order to characterize the non‐statistical properties based on the possibility theory [2]. A linear elastic body with fuzzy input material parameters Young's modulus$\tilde{E}$ and Poisson's ratio$\tilde{ν}$ is studied. To this end, the fuzzy parameters are represented by possibility distributions generated from sparse experimental data. A computational approach involving the α‐level discretization technique [4] is used in order to calculate the possibility of the system response. Finally, our method is applied in a numerical example. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)